2017
DOI: 10.1158/0008-5472.can-16-2784
|View full text |Cite
|
Sign up to set email alerts
|

STING Activation Reverses Lymphoma-Mediated Resistance to Antibody Immunotherapy

Abstract: Tumors routinely attract and co-opt macrophages to promote their growth, angiogenesis and metastasis. Macrophages are also the key effector cell for monoclonal antibody (mAb) therapies. Here we report that the tumor microenvironment creates an immunosuppressive signature on tumor-associated macrophages (TAM) which favors expression of inhibitory rather than activating Fcγ receptors (FcγR), thereby limiting the efficacy of mAb immunotherapy. We assessed a panel of TLR and STING agonists (a) for their ability to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 50 publications
7
63
0
Order By: Relevance
“…Furthermore, our in vitro observations also allowed us to dissect the specific effect of IFN-γ, IFN-I and TNF-α on the enhancement of the functional properties of IC-activated neutrophils and monocytes. Notably, IFN-γ and IFN-I priming (but not TNF-α), led to the upregulation of FcγRs in neutrophils and/or monocytes, in agreement with previous reports in other experimental settings (Dahal et al, 2017; Lehmann et al, 2017; Morquin et al, 2017; Pricop et al, 2001). Consistent with these results, our in vivo work shows that the inflammatory environment resulting from ongoing infection and mAb-treatment also modulates FcγRs expression on neutrophils and monocytes (in particular FcγRIV).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, our in vitro observations also allowed us to dissect the specific effect of IFN-γ, IFN-I and TNF-α on the enhancement of the functional properties of IC-activated neutrophils and monocytes. Notably, IFN-γ and IFN-I priming (but not TNF-α), led to the upregulation of FcγRs in neutrophils and/or monocytes, in agreement with previous reports in other experimental settings (Dahal et al, 2017; Lehmann et al, 2017; Morquin et al, 2017; Pricop et al, 2001). Consistent with these results, our in vivo work shows that the inflammatory environment resulting from ongoing infection and mAb-treatment also modulates FcγRs expression on neutrophils and monocytes (in particular FcγRIV).…”
Section: Discussionsupporting
confidence: 92%
“…reported to display increased phagocytosis and other markers of macrophage activation; they also recruit new macrophages which serve a phagocytic role in the TME [41][42][43][44] . Consistent with these observations we confirmed that HMDMs transfected with c-di-AMP showed increased phagocytosis and exhibited elongated dendrites compared to mock-transfected populations ( Fig.…”
Section: Macrophages Exposed To Sting Agonists Delivered By Intratumomentioning
confidence: 99%
“…So‐called Danger signals provided by TLR activation enable effective FcγR A:I ratio skewing, but their efficacy in vivo is limited. For instance, the TLR1/2 agonist Pam3CSK4 robustly induced favourable FcγR A:I changes, inflammation and phagocytosis of target cells in vitro, but failed to achieve this in vivo . Therefore, drugs such as UC‐1V150 that promote appropriate FcγR expression profiles in vivo, with the potential for murine to human translation raise the possibility of providing synergistic treatments with existing antibody therapeutics.…”
Section: Resultsmentioning
confidence: 99%
“…We recently examined the potential of a range of TLR agonists for their ability to activate innate immune cells, including mouse and human macrophages, to improve mAb‐mediated immunotherapy . Although Imiquimod demonstrated some activity, it was unable to significantly augment mAb‐immunotherapy.…”
Section: Introductionmentioning
confidence: 99%